1997
DOI: 10.1091/mbc.8.12.2463
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Class I Human Leukocyte Antigen (HLA-I) Molecules with Insulin Receptors and Its Effect on the Insulin-Signaling Cascade

Abstract: Insulin receptor (IR) and class I major histocompatibility complex molecules associate with one another in cell membranes, but the functional consequences of this association are not defined. We found that IR and human class I molecules (HLA-I) associate in liposome membranes and that the affinity of IR for insulin and its tyrosine kinase activity increase as the HLA:IR ratio increases over the range 1:1 to 20:1. The same relationship between HLA:IR and IR function was found in a series of B-LCL cell lines. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 74 publications
2
58
0
1
Order By: Relevance
“…The best characterized non-immune interaction of MHC class I is with the IR. It has been suggested that MHC class I molecules are involved in glycosylation of IR and its proper transport to the cell surface, but most evidence has been provided for the role of MHC class I in insulin-induced IR internalization (Olsson et al 1994, Ramalingam et al 1997, Stagsted 1998, Stagsted et al 1993a, Stagsted et al 1990, Stagsted et al 1993b. A number of studies have suggested that MHC class I associates with IR after insulin binding thereby causing its internalization and removal from the cell surface.…”
Section: Mhc Class I Signaling In Immune and Non-immune Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best characterized non-immune interaction of MHC class I is with the IR. It has been suggested that MHC class I molecules are involved in glycosylation of IR and its proper transport to the cell surface, but most evidence has been provided for the role of MHC class I in insulin-induced IR internalization (Olsson et al 1994, Ramalingam et al 1997, Stagsted 1998, Stagsted et al 1993a, Stagsted et al 1990, Stagsted et al 1993b. A number of studies have suggested that MHC class I associates with IR after insulin binding thereby causing its internalization and removal from the cell surface.…”
Section: Mhc Class I Signaling In Immune and Non-immune Systemsmentioning
confidence: 99%
“…characterized by a low basal transmission which is www.intechopen.com maintained by activation of a number of receptors that have inhibitory effects on synaptic transmission (Nicoll and Schmitz 2005). As previously mentioned, given that the best characterized non-immune function of MHC class I is regulation of trafficking and internalization of various receptors (Olsson et al 1994, Stagsted 1998, Stagsted et al 1990, Ramalingam et al 1997, it is likely that neuronal MHC class I molecules in the marmoset hippocampus are needed for proper internalization of one or several of those receptors (Figure 8). One may speculate that blocking the interaction of MHC class I with such Fig.…”
Section: Molecular Mechanisms Of Neuronal Mhc Class I Actionmentioning
confidence: 99%
“…M ajor histocompatibility complex class I (MHC-I) 3 molecules are trimeric structures of a 44-to 49-kDa H chain, a 12-kDa L chain named ␤ 2 -microglobulin (␤ 2 m), and a 9-to 11-aa peptide. MHC-I molecules are folded and assembled inside the endoplasmic reticulum (ER) with the aid of several chaperones and accessory molecules such as calnexin, calreticulin, tapasin, and ERp57, and are ultimately transported to the cell surface of almost all nucleated cells (1).…”
mentioning
confidence: 99%
“…MHC-I molecules are folded and assembled inside the endoplasmic reticulum (ER) with the aid of several chaperones and accessory molecules such as calnexin, calreticulin, tapasin, and ERp57, and are ultimately transported to the cell surface of almost all nucleated cells (1). In addition to their role in presenting peptides to CD8 ϩ CTLs, cell surface MHC-I molecules have been implicated in receptor-mediated endocytosis (2)(3)(4).…”
mentioning
confidence: 99%
“…It has been reported in a number of studies that direct interactions between MHC glycoproteins and the IR were found to enhance ligand-induced internalization of the receptor (18). Other investigators have shown that the ratio between membrane-expressed MHC class I glycoproteins and IR molecules determines the extent of ligand-induced phosphorylation of the IR and the IR substrate-1 and, as well, the recruitment of phosphatidylinositol 3-kinase to the plasma membrane (11). The aforementioned findings suggest that MHC class I glycoproteins may play an important role in growth factor-mediated cell-cell communication and in receptor-mediated signal transduction; both of these processes are significantly impaired during malignant transformation and tumor progression.…”
mentioning
confidence: 99%